Analiza bazy SAGE Journals Online: publikacje przypisane do słowa kluczowego bibliotherapy - Chatzipentidis, Kiriakos (2017)
The article will examine SAGE Journals Online database titles assigned to the keyword „bibliotherapy”. There will be presented the bibliography of bibliotherapeutic literature available in SAGE Journals Online database.
Keywords: bibliotherapy literature; bibliotherapy research; bibliotherapy; SAGE Journals Online